Exhausted Tea Leaves – a low cost bioadsorbent for the removal of Lead (II) and Zinc (II) ions from their aqueous solution - Shrestha, Bindra; Homagai, P. L.; Pokhrel, M. R.; Ghimire, K. N. (Journal of Nepal Chemical Society, 2013)
An efficient and cost effective bioadsorbent has been prepared from exhausted tea leaves using hydrazine monohydrate. The aminated tea leaves (ATL) was characterised by elemental and spectral analysis. The batch adsorption study was performed using ATL for the removal of Pb++ and Zn++ from their aqueous solution. Adsorption experiment was conducted as the function of solution pH, initial metal concentration and contact time. The maximum adsorption capacity of the adsorbent was found to be 120.8 mg/g for Pb++ and 79.76 mg/g for Zn++. These results indicated that the aminated tea leaves hold great potential to remove Pb++ and Zn++ from aqueous solution. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9383 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 123-129 Uploaded date: 12/20/2013